7y+5=9y

Simple and best practice solution for 7y+5=9y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y+5=9y equation:


Simplifying
7y + 5 = 9y

Reorder the terms:
5 + 7y = 9y

Solving
5 + 7y = 9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-9y' to each side of the equation.
5 + 7y + -9y = 9y + -9y

Combine like terms: 7y + -9y = -2y
5 + -2y = 9y + -9y

Combine like terms: 9y + -9y = 0
5 + -2y = 0

Add '-5' to each side of the equation.
5 + -5 + -2y = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -2y = 0 + -5
-2y = 0 + -5

Combine like terms: 0 + -5 = -5
-2y = -5

Divide each side by '-2'.
y = 2.5

Simplifying
y = 2.5

See similar equations:

| 36.86=7g+3.54 | | -16-2n=n-4 | | 3(x+2)-7x=9(x-18)+9x-2 | | (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 | | 1+3m=m+7 | | 4x+3=5(x-11) | | 52=10+c | | 4y+8x=13 | | -3+6m=15-3m | | 2=-17+c | | 7x+50=5x-14 | | 2a+7=5a+1 | | -0.231p=-2 | | 26-9x=10+7x | | -5x+15=-2x+3 | | 3a+4=6a-2 | | 2x^2+mx+3=x+1 | | f(x)=12+3x | | 12y+11=6y+41 | | 11y-6=93 | | 6(6-6n-3)+3=8n+29 | | 13+3p=7-3p | | 3(x+2)=7(x-2) | | 0.625y-7=-2 | | -5(r+6)=-84 | | 3+5b=3b-1 | | 2[-(x-1)+4]=5+[-(6-7)+9x] | | -7-8r=1-6r-4 | | 8x+7x-66=110-7x |

Equations solver categories